Strengthening Community Mental Health Systems: Evidence from Interventions for Families Left Behind by Migrant Workers (Spectrum of Humanities and Social Sciences, 2025)
This study aimed to strengthen community mental health systems, increase mental health service access and promote community resilience. A mixed-methods cross-sectional evaluation was conducted in seven municipalities of Salyan and Kailali districts. Quantitative data were collected from 91 participants, representing a subsample of baseline respondents, using structured questionnaires. Qualitative data were gathered through 20 key informant interviews (KIIs) with health workers, local government representatives, and project staff, and four focus group discussions (FGDs) with beneficiaries. Data were analyzed using descriptive statistics for the quantitative component and thematic analysis for the qualitative component. Findings revealed reduced stigma, increased community awareness, and stronger coordination between local authorities and service providers. The project significantly contributed to mental health system strengthening, building Mental health and psychosocial services (MHPS) service, and community development by integrating mental health into primary health care system, empowering local stakeholders, and fostering social inclusion. These findings underscore the potential for scaling up similar community-based mental health interventions to enhance wellbeing and resilience in low-resource settings.